Investigating the Role of Religiosity and Spirituality in Shaping Attitudes Toward Homosexuality Among Muslim Youth in Pakistan - Kainat Zia (Corresponding Author); Inayat Shah; Erum Bibi; Jawahir Mumtaz; Bushra Hakim (Journal of Religion and Society, 2025)
This study aimed to investigate the role of religiosity and spirituality in shaping attitudes toward homosexuality among Muslim youth in Pakistan. Using a cross-sectional design, data were collected from 246 participants aged 18–29 years through standardized tools (the Homosexuality Attitude Scale, the Religiosity and Spirituality Scale for Youth). Descriptive statistics revealed moderate levels of religiosity and spirituality and an overall moderate to low acceptance of homosexuality. Independent samples t-tests indicated significant gender and marital status differences, with females and unmarried individuals demonstrating more favorable attitudes toward homosexuality. Pearson correlation analysis showed a significant negative relationship between religiosity and positive attitudes toward homosexuality, while spirituality showed a weak but positive correlation. Multiple regression analysis revealed that religiosity was a strong negative predictor of attitudes toward homosexuality. Overall, 27.8% of the variance in attitudes was observed. The findings highlight the significant role of religious orientation in shaping moral and social perspectives on homosexuality in a religiously driven society. These insights have implications for policymakers, educators, and mental health practitioners addressing sexual diversity among youth in Pakistan. Keywords: Religiosity, Spirituality, Attitudes Formation, Homosexuality, Muslim Youth